Flying squad response to out-of-hospital cardiac arrest--a decade of experience. Issue 2 (June 1992) - Cusack, S; Steedman, D J; Robertson, C E; Little, K
Abstract : The Flying Squad (MEDIC I) based at the Royal Infirmary, Edinburgh, commenced operation in 1980. The MEDIC I response to out of hospital non-traumatic cardiac arrest over the past decade is reported. On-scene resuscitation was attempted in 384 patients. A total of 149 (39%) patients were successfully resuscitated and transferred to hospital. Thirty-six (9.4%) patients survived to discharge from hospital. Patients receiving basic life support prior to the arrival of MEDIC I and in ventricular fibrillation had a survival rate of 14.5% (25/174). During 1988-89, 21 patients were initially attended by ambulance crews equipped with semi-automatic external defibrillators and eight (38%) of these patients survived. The response of a hospital-based flying squad to support trained ambulance crews, especially when equipped with a defibrillator may provide an economically and operationally feasible alternative to training all first responders in the full range of paramedic skills.